Effects of uteroplacental insufficiency on growth-restricted rats with altered lung development: A metabolomic analysis - Yuliana, Merryl Esther; Huang, Zheng-Hao; Chou, Hsiu-Chu; Chen, Chung-Ming (Frontiers in Pediatrics, 2022)
Background: Intrauterine growth restriction (IUGR) is among the most challenging problems in antenatal care. Several factors implicated in the pathophysiology of IUGR have been identified. We aimed to investigate the effect of UPI on lung development by identifying metabolic changes during the first seven days of postnatal life. Materials and Methods: On gestation day 17, four time-dated pregnant Sprague Dawley rats were randomized to a IUGR group or a control group, which underwent an IUGR protocol comprising bilateral uterine vessel ligation and sham surgery, respectively. On gestation day 22, 39 control and 26 IUGR pups were naturally delivered. The rat pups were randomly selected from the control and IUGR group on postnatal day 7. The pups’ lungs were excised for histological, Western blot, and metabolomic analyses. Liquid chromatography mass spectrometry was performed for metabolomic analyses. Results: UPI induced IUGR, as evidenced by the IUGR rat pups having a significantly lower average body weight than the control rat pups on postnatal day 7. The control rats exhibited healthy endothelial cell healthy and vascular development, and the IUGR rats had a significantly lower average radial alveolar count than the control rats. The mean birth weight of the 26 IUGR rats (5.89 ± 0.74 g) was significantly lower than that of the 39 control rats (6.36 ± 0.55 g; p< 0.01). UPI decreased the levels of platelet-derived growth factor-A (PDGF-A) and PDGF-B in the IUGR newborn rats. One-way analysis of variance revealed 345 features in the pathway, 14 of which were significant. Regarding major differential metabolites, 10 of the 65 metabolites examined differed significantly between the groups (p< 0.05). Metabolite pathway enrichment analysis revealed significant between-group differences in the metabolism of glutathione, arginine–proline, thiamine, taurine–hypotaurine, pantothenate, alanine–aspartate–glutamate, cysteine–methionine, glycine–serine–threonine, glycerophospholipid, and purine as well as in the biosynthesis of aminoacyl-tRNA, pantothenate, and CoA. Conclusions: UPI alters lung development and metabolomics in growth-restricted newborn rats. Our findings may elucidate new metabolic mechanisms underlying IUGR-induced altered lung development and serve as a reference for the development of prevention and treatment strategies for IUGR-induced altered lung development.